Politics at a distance from the state: radical, South African and Zimbabwean praxis today. Issue 3 (2nd July 2016) - Helliker, Kirk; van der Walt, Lucien
ABSTRACT: For decades, most anti-capitalist and anti-imperialist movements identified radical social transformation with the capture of state power. The collapse of supposedly enabling states led recently to a crisis of left and working class politics. But this has also opened space for the rediscovery of society-centred, anti-capitalist modes of bottom-up change, labelled as 'at a distance' politics. These modes have registered important successes in practice, such as the Zapatistas in Mexico, and have involved strands of anarchism and syndicalism, and autonomist Marxism. This article, an introduction to a collection of papers emerging from a 2012 conference of academics and activists in South Africa, aims to help articulate an understanding of social transformation from below that has been analytically and politically side-lined not only in South Africa (and Zimbabwe), but globally. In doing so, it provides a preliminary attempt to map and create a dialogue between three major positions within the broad category of 'at a distance' politics.